Ediacaran Doushantuo-type biota discovered in Laurentia - Willman, Sebastian (Commun Biol, 2020)
The Ediacaran period (635–541 Ma) was a time of major environmental change, accompanied by a transition from a microbial world to the animal world we know today. Multicellular, macroscopic organisms preserved as casts and molds in Ediacaran siliciclastic rocks are preserved worldwide and provide snapshots of early organismal, including animal, evolution. Remarkable evolutionary advances are also witnessed by diverse cellular and subcellular phosphatized microfossils described from the Doushantuo Formation in China, the only source showing a diversified assemblage of microfossils. Here, we greatly extend the known distribution of this Doushantuo-type biota in reporting an Ediacaran Lagerstätte from Laurentia (Portfjeld Formation, North Greenland), with phosphatized animal-like eggs, embryos, acritarchs, and cyanobacteria, the age of which is constrained by the Shuram–Wonoka anomaly (c. 570–560 Ma). The discovery of these Ediacaran phosphatized microfossils from outside East Asia extends the distribution of the remarkable biota to a second palaeocontinent in the other hemisphere of the Ediacaran world, considerably expanding our understanding of the temporal and environmental distribution of organisms immediately prior to the Cambrian explosion.